Working beyond pension age in Turkey :|a qualitative analysis from a life course perspective - Kösem, Mine. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
Working in later life is increasingly becoming the norm in contemporary societies. Current developments in labor market and pension policies have extended working lives. This thesis focuses on the emerging pattern of working beyond retirement age in Turkey. It provides answers to the following questions: How do older workers in Turkey explain their reasons to continue working beyond the retirement age? What factors do they perceive as accounting for their continued employment? To what extent do they see their continued employment as an obligation or a choice? This thesis relies on 25 semi-structured in-depth interviews that were conducted between April and June 2021 with individuals who are 55 yearsold or above. Based on a qualitative thematic analysis of the interviews from a life- course perspective, the findings of this thesis reveal the complexity of factors in explaining respondents' decision to continue working beyond the retirement age in the case of Turkey. These factors, spread out over the course of life, cut across multiple levels, such as changes in the welfare system and the labor market, household needs, and individual motivations. Last butnot the least, this thesis suggests that the narratives of working in later life are also indicative of the individualization of the risk of income loss in old age in the Turkish context.
Keywords: Retirees -- Employment -- Turkey.; Post-retirement employmenty -- Turkey.; Older people -- Employment -- Turkey.